Symptomatic, Unstable Os Acromiale. Issue 22 (15th November 2018) - Hasan, S. Ashfaq; Shiu, Brian; Jauregui, Julio J.
Abstract : Management of a persistently symptomatic, unstable os acromiale remains controversial. An unstable os acromiale is an easy diagnosis to miss and should be specifically evaluated for in patients with shoulder pain and a high degree of clinical suspicion. Surgical options include open or arthroscopic excision and open reduction and internal fixation. Open excision of large fragments has had poor results. Arthroscopic treatment is commonly used for small fragments (preacromion), and the technique has also been used in larger fragments (meso-os), but concerns persist over postoperative weakness secondary to shortening of the deltoid lever arm. Open reduction and internal fixation through a transacromial approach has been shown to have predictable union rates but can be complicated by symptomatic implant. Recent biomechanical studies have expanded our understanding of optimal fixation constructs, which may also decrease implant-related issues. Ultimately, the choice of which procedure to use will be dictated by patient factors such as age, activity level, and the nature of rotator cuff pathology. Level of Evidence: Level V